Drug Discovery for Overcoming Chronic Kidney Disease (CKD): New Therapy for CKD by a (Pro)Renin-Receptor–Blocking Decoy Peptide - Atsuhiro Ichihara (Journal of Pharmacological Sciences, 2009)
Discovery of the (pro)renin receptor uncovered a novel function of renin/prorenin as the receptor ligands in addition to the enzyme and its precursor. The bindings of renin and prorenin to the (pro)renin receptor trigger two major pathways: the angiotensin II–dependent pathway as a result of the enzymatic activation of renin/prorenin and the angiotensin II– independent intracellular pathway involving hypertrophic, hyperplastic, and profibrotic signals. A specific blocker of the receptor was discovered through identification of the amino acid sequence of prorenin prosegment that binds to the receptor and leads to non-proteolytic conversion of prorenin to its active form. A peptide containing this sequence was found to block the binding of prorenin to its receptor. Its infusion in animal models of diabetes and low-renin hypertension significantly inhibited the development and progression of nephropathy, but (pro)renin receptor blockade had no benefit in the clipped kidney of 2K1C rats or rat models of high-renin hypertension. Since renin is still active without a (pro)renin receptor, (pro)renin-receptor blockade elicits a maximum benefit under low-renin conditions. Thus, (pro)renin-receptor blockade can be a useful therapy for chronic kidney disease with low renin levels in the plasma. Keywords:: angiotensin, diabetes, hypertension, mitogen-activated protein kinase, renin, chronic kidney disease (CKD)